Transcribing and translating forensic speech evidence containing foreign languages—An Australian perspective - Lai, Miranda (Frontiers in Communication, 2023)
There is a growing body of literature on forensic transcription of covert recordings obtained by clandestine law enforcement operations. Due to the nature of these operations, the quality of the recordings, particularly those obtained by planting listening devices in a car or a house, is often extremely poor. When tendering such recordings as evidence in court for prosecuting an alleged crime, a transcript will often accompany the recording to assist the triers of fact (i.e., judges and jurors) to hear better. In the context of multilingual and multicultural Australia, often such forensic recordings may contain languages other than English, and therefore a translation into English of the utterances in the recording is required to facilitate understanding of the verbal exchanges. Little is known, however, about the people engaged by law enforcement to undertake these forensic translation tasks, what qualification and training they possess, how they carry out the tasks, and if there is a system to safeguard the quality and reliability of their translation output. This paper reports on the first ever survey conducted in Australia on professional interpreters and translators who have been engaged to perform this type of work. Descriptive statistics and thematic analysis of text answers provide a qualitative account of the status quo which has not been documented before. Deficiencies of the current practice and its associated risks are identified. Possible solutions are proposed to address the issues identified.